Optimization Of Village Fund Optimization Of Village Fund Allocation In The Development Of Religious-Based Tourism Villages In Senduro Village, Lumajang Regency - Sholahudin, Umar; Abdus Sa'ir (International Journal of Education, Vocational and Social Science, 2026)
This article examines the optimization of Village Fund Allocation (Alokasi Dana Desa/ADD) in the development of a religious-based tourism village in Senduro Village, Lumajang Regency. Village Fund Allocation (ADD) is a village fiscal policy instrument aimed at promoting village independence through development, community empowerment, and strengthening the local economy. This article aims to analyze the optimization of ADD use in the development of a religious-based tourism village in Senduro Village, Lumajang Regency. The research employs a descriptive-qualitative approach using the case study method. Data was collected through field observation, in-depth interviews with religious leaders, community figures, and residents of various faiths, as well as supporting documentation. Data was analyzed qualitatively using triangulation techniques to gain a comprehensive and in-depth understanding. The results indicate that ADD in Senduro Village has been utilized as a stimulus for the development of religious tourism by focusing on strengthening supporting infrastructure, facilitating cultural and religious activities, and community empowerment based on local social capital. The presence of the Mandara Giri Semeru Agung Temple, the Ogoh-Ogoh Festival, Grebeg Suro, and the Sedekah Bumi (Jolen) tradition serve as major religious tourism attractions that not only strengthen the village's social and cultural identity but also provide economic impacts for the community through the growth of people's businesses and home industries. Although the ADD allocation for religious tourism activities is relatively limited in nominal terms, it has managed to generate a multiplier effect thanks to the high levels of participation, mutual cooperation (gotong royong), and interfaith tolerance deeply embedded in the social life of Senduro Village. This finding confirms that ADD optimization is not solely determined by the budget amount, but rather by the effectiveness of management, community participation, and the village's ability to integrate economic development with social, cultural, and religious values. Therefore, the development of the religious-based tourism village in Senduro can be viewed as a model of sustainable, inclusive village development oriented towards socio-economic independence.